Modelling of Indoor Positioning Systems Based on Location Fingerprinting - Nicholaus, Mrindoko R.; Nfuka, Edephonce; Aliila, Kenedy A. (International Journal of Computer (IJC), 2020)
In recent years, localization systems for indoor vicinity using the present wireless local area (WLAN) network infrastructure have been proposed. Such positioning systems create the usage of location fingerprinting instead of direction or time of arrival techniques for deciding the location of mobile users. However experimental study associated to such localization systems have been proposed, high attenuation and signal scattering related to greater density of wall attenuation still affecting the indoor positioning performance. This paper presents an analytical model for minimizing high signal attenuation effect for WLAN fingerprinting indoor positioning systems. The model employs the probabilistic algorithm that using signal relation method.